Science Journalism in the Post-COVID-19 Landscape: A Bibliometric Systematic Review Through the Lens of Post-Normal Science - Saputro, Imam; Hastjarjo, Sri; Anggreni, Likha Sari (Universitas Muhammdiyah Yogyakarta, 2026)
This study aims to explore publication in science communication in collaboration with journalism. Using a Bibliometric-Systematic Literature Review (B-SLR) with the PRISMA protocol, bibliometric data were collected from the Scopus database and analyzed using Bibliometrix and VOSviewer tools to visualize citation networks, co-authorship, and thematic clusters. The analysis covered 85 peer-reviewed articles published between 2007 until 2025. Results reveal a steady rise in publication volume, with a significant surge between 2020 and 2023, coinciding with the COVID-19 pandemic and the heightened need for credible, evidence-based science journalism. Major contributors are concentrated in the Global North, particularly the United States, Germany, and the United Kingdom, while Asia’s participation especially Japan, China, and India are growing. Southeast Asian countries, including Indonesia, remain underrepresented. Thematically, five main clusters emerge: pandemic communication, methodological and public trust studies, science journalism training, media perception, and storytelling approaches. The main finding of this study is that science communication is undergoing a paradigm shift towards a Post-Normal Science model, but this transformation remains dominated by the Global North and has not been balanced by an inclusive epistemic distribution, especially in Southeast Asia. Overall, science communication has evolved into an increasingly inclusive and multidisciplinary international research field. Nonetheless, this study is limited by its reliance on indexed publications, which may introduce geographical and linguistic bias, especially the underrepresentation of non-English publications.